Awakening expectations: exploring social and ethical issues surrounding the medical and non-medical uses of cognition enhancing drugs in the UK - Coveney, Catherine M. (2010)
The aim of this thesis is to explore the social and ethical issues surrounding the use of neurotechnologies to control sleep and enhance cognition in British society. Empirically, the project is based on a case study of the wake-promoting drug modafinil. Data analysis involved the study of a corpus of 77 UK news articles and 40 semi-structured interviews with three stakeholder groups: scientists and clinicians, shift workers and students. The analytical framework used was informed by previous work in both medical sociology and bioethics and developed using key concepts drawn from Science and Technology Studies. Conceptualising modafinil as a sociotechnical object, different discourses surrounding sleep, cognitive enhancement and pharmaceutical use were explored to assess how sociotechnical spaces for ‘therapy’ and ‘enhancement’ are being constructed and negotiated in different domains of social life.